Analysis of Green Sukuk Initiatives for Increasing Non-Tax Profit-Sharing Funds and Alleviating Poverty in Rural Areas - Agung Budilaksono (Journal of Accounting and Finance Management, 2025)
This study addresses the issue of limited empirical evidence regarding the tangible impact of Green Sukuk on regional finances and rural poverty in Indonesia, despite the instrument's implementation since 2018. The research aims to measure and analyze the impact of Green Sukuk on increasing Non-Tax Revenue Sharing Funds (DBH Non-Pajak) and reducing poverty in rural areas during the 2018-2024 period. Quantitative data were collected from official sources, including Green Sukuk allocations (Ministry of Finance), rural poverty percentages (BPS), and DBH Non-Pajak realizations (Directorate General of Fiscal Balance). The analytical method employs the Truncated Derivative approach with the estimation of two separate linear regression models to measure the rate of change (RDY) of dependent variables relative to changes in Green Sukuk. Data processing results indicate that Green Sukuk has a significant and positive impact: every increase of 1 trillion Rupiah in average Green Sukuk reduces the poverty change rate by 0.215% (p=0.032) and increases the DBH Non-Pajak change rate by 4.128% (p=0.041), with model explanatory power of 89.2% and 78.5%, respectively. The study concludes by confirming the effectiveness of Green Sukuk as a double dividend instrument that simultaneously promotes social justice and regional fiscal resilience, thereby necessitating optimized policy for allocation and distribution that is more integrated with regional development.